Synthesis and structure of lanthanides iodide complexes with iodine and carbamide. - L. Yu. Alikberova; N. N. Mishin; A. I. Mytareva; N. S. Rukk (Тонкие химические технологии, 2008)
Complexes of lanthanum, cerium, neodymium, samarium, europium, terbium, erbium, thulium, ytterbium, lutetium iodides with carbamide and iodine were synthesized and characterized by chemical analyses, IR and Raman spectroscopy, electric conductivity (from –195.,8 to 20°С). These compounds are found to include complex cations and polyiodide anions.